3504 Metagenomic characterization of influenza virus: bacteria super-infections associated with death and survival. (27th March 2019) - Klonoski, Josh; Williams, Matthew; Huber, Victor
Abstract : OBJECTIVES/SPECIFIC AIMS: To better understand host, viral and bacterial responses underlying disparate outcome. METHODS/STUDY POPULATION: We utilized metagenomic analysis of 559 genes, the NanoString nCounter Immunology Panel-Plus kit and FFPE mouse lungs from a published BSI time course. RESULTS/ANTICIPATED RESULTS: Results show an overall increased level of gene expression during BSIs associated with survival when compared to gene expression during peak viral titers. Early viral clearance and the presence of S. pyogenes in the lungs of TX98 infected lungs 24 hours after BSI was confirmed. Host responses tied to differences in early viral detection and clearance consisted of RIG-I, OAS, TLR3, TLR8 and TLR9. Key changes were noted in the expression of type I and II interferons, complement proteins, cytokines, chemokines, Fc receptors, scavenger receptors, the immunoproteasome and genes associated with T, B, Treg and NK cell activation. Interestingly, there was no significant increase in host antimicrobial peptides during BSIs associated with survival while CAMP and Nos2 were significantly increased 24hrs prior to death in lethal BSIs. DISCUSSION/SIGNIFICANCE OF IMPACT: To our knowledge this is the first side by side metagenomics study of influenza BSIs associated with death and survival. Results offer mechanistic insight into clinical outcomes.